John Wright and Aron Mazel, Tracks in a Mountain Range. Exploring the History of the Ukhahlamba-Drakensberg Wits University Press, Johannesburg, 2007: Blood, Sweat and Tears in a Mountain Range (Historia, 2021)
The Unesco Declaration of the Drakensberg World Heritage Site celebrates scenic beauty, biodiversity and the cultural value of an exceptional rock art heritage. Tracks in a Mountain Range, on the other hand, does not celebrate. Instead, it depicts struggles of all kinds : culture against nature, settlers against autochthones, British against Boer, indigenous kingdoms against one another, rich against poor, conservationist versus farmer. This study portrays the Berg's real history, not the Disneyland version of tourism brochures. You will find neither hunter-gatherer romanticism and nostalgic, nor epic stories of pioneer heroism. The protagonists of this narrative are land-hungry farmers and power-crazy leaders, scheming magistrates, rebellious chiefs, raiders and traders, hunters and hunted. Blood, Sweat and Tears in a Mountain Range might have been a more appropriate title for this study.